Fundamental and Macroeconomic Factors on Manufacturing Companies’ Stock Returns - Pratiwi, Siska Gita; Robiyanto, Robiyanto; Martono, Samuel (Universitas Pendidikan Ganesha, 2021)
Investments are made to obtain future benefits. Stocks are one of the most popular investments in the capital market. The advantage that can be obtained from the stock investment is stock returns, where the returns obtained can be positive or negative. This study aims to analyze the influence of fundamental and macroeconomic factors on stock returns of manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2019. This study used secondary data and the sample of this research was 37 manufacturing companies obtained through the purposive sampling method with panel regression as the data analysis. The results showed that the fundamental factors that affect stock returns are Price to Book Value (PBV), while the Debt to Equity Ratio (DER) and Price to Earnings Ratio (PER) do not affect manufacturing stock returns. Some macroeconomic factors such as inflation, the BI Rate, and changes in world oil prices proved to not affect the stock returns of manufacturing companies. This research implies that manufacturing companies need to pay attention to Price to Book Value (PBV) in determining stock returns.